Editorial Changes - Editor, (PINS-Psychology in Society, 2017)
Every two to three years PINS “renews” its Editorial group. This allows current editors to commit to staying on the journal’s editorial group, or to move off to pursue other intellectual interests. This process ensures that the editorial group members who choose to stay on continue to devote some time and energy to the running of the journal. As an independent journal, with no infrastructural support, PINS relies on the “free labour” of editors to contribute to its production and continued sustainability. The editorial renewal also allows PINS to approach new people to join the editorial group. This new Editorial group is an exciting mix of experience, innovative ideas, and scholarly commitment to psychological theory and practice that is socially embedded in the society in which it operates. In their hands, the social project of PINS should be well served.